Photocontrolled miR-148b nanoparticles cause apoptosis, inflammation and regression of Ras induced epidermal squamous cell carcinomas in mice. (October 2020) - Liu, Yiming; Bailey, Jacob T.; Abu-Laban, Mohammad; Li, Shue; Chen, Cong; Glick, Adam B.; Hayes, Daniel J.
Abstract: Despite evidence that microRNAs (miRNAs) are essential in modulating tumorigenesis, a major challenge in cancer treatment is to achieve tumor-specific selectivity and efficient yet safe delivery of miRNAs in vivo . In this study, we have developed a light-inducible silver nanoparticle nucleic acid delivery system that demonstrates precise spatiotemporal control, high cellular uptake, low cytotoxicity, escape from endosomes and release of functional miRNA into the cytosol. Using this approach, we delivered exogenous miR-148b to induce apoptosis in Ras-expressing keratinocytes and murine squamous cell carcinoma cells while avoiding cytotoxicity in untransformed keratinocytes. When administered to transgenic mice with HRas G12V -driven skin tumors, a single dose of silver nanoparticle conjugates followed by 415 nm LED irradiation at the tumor site caused a rapid and sustained reduction in tumor volume by 92.8%, recruited T cells to the tumor site, and acted as a potent immunomodulator by polarizing the cytokine balance toward Th1 both locally and systemically. In summary, our results demonstrate that spatiotemporal controlled miR-148b mimic delivery can promote tumor regression efficiently and safely. Graphical abstract: Image 1